Surpassing the 10% efficiency milestone for 1-cm(2) all-polymer solar cells - Fan, Baobing (Nat Commun, 2019)
Naphthalenediimide-based n-type polymeric semiconductors are extensively used for constructing high-performance all-polymer solar cells (all-PSCs). For such all-polymer systems, charge recombination can be reduced by using thinner active layers, yet suffering insufficient near-infrared light harvesting from the polymeric acceptor. Conversely, increasing the layer thickness overcomes the light harvesting issue, but at the cost of severe charge recombination effects. Here we demonstrate that to manage light propagation within all-PSCs, a thick bulk-heterojunction film of approximately 350 nm is needed to effectively enhance photo-harvesting in the near-infrared region. To overcome the severe charge recombination in such a thick film, a non-halogenic additive is used to induce a well-ordered micro-structure that inherently suppresses recombination loss. The combined strategies of light management and delicate morphology optimization lead to a promising efficiency over 10% for thick-film all-PSCs with active area of 1 cm(2), showing great promise for future large-scale production and application of all-PSCs.